What is left of BreadTube? Researching YouTube-based political cultures with Situational Analysis - Liedtke, Marius (AoIR Selected Papers of Internet Research, 2026)
This contribution investigates the case of “BreadTube”, a left-wing counterpublic that first formed on YouTube in opposition to the dominance of right-wing voices and networks on the platform. To gain a better understanding of the inner workings of this media-based collectivity, this article analyzes an internal controversy to reconstruct the tacit assumptions of various participants about the counterpublic’s aims, values, shortcomings as well as its economic and technological prerequisites. To capture the controversy for exploration, an innovative approach was employed that adapts Clarke’s Situational Analysis as a framework to integrate both interpretative mapping and computational network analysis to properly account for the videos high level of intertextual referentiality as well as their algorithmic interrelatedness. This digitally and visually enhanced Situational Analysis framework was able to deliver a comprehensive insight into the complex and dynamic constellation of perspectives and segments BreadTube is composed of and illuminated arenas in which adverse interests overlap and conflict arises over questions of representation, legitimacy, shared history, and resource allocation.